THE STUDENTS’ SELF-DIRECTED LEARNING IN ENGLISH LEARNING ON THE ELEVENTH-GRADE OF SMA NEGERI 1 TEMBILAHAN - Nurbaiti; Agus Mustajib; Maizarah (Program Studi Pendidikan Bahasa Inggris, 2021)
The purpose of this research is to know the level of students' self-directed learning in English learning on eleventh-grade students of SMA Negeri 1 Tembilahan. This research was achieved by conducting a descriptive quantitative study. The total population of this research was 268 students. Sample of this research were 92 students of eleventh-grade students of SMAN 1 Tembilahan. The researcher used purposive sampling to take the sample. The researcher gave a questionnaire to collect data, consisting of 20 statements based on self-directed learning indicators. It was using the Likert Scale. The results revealed that students' self-directed learning in English learning relies on enough levels with 63,97%. It means that they have a problem being a self-directed learner in English learning. They need to improve themselves to become a self-directed learner. The role of the teacher is vital in order to guide them to be more independent. The teacher can provide the instructions needed to direct students' initiative in their learning process to be more independent.